Pina Bausch's dance theater company, artistic practices and reception - Klein, Gabriele 1957- (TanzScripte, 2020)
Pina Bausch and Dance Theater. The Art of Translating offers new and ground-breaking perspectives on the work of the Tanztheater Wuppertal. The development and performance of its oeuvre, the passing on of choreographic material and reactions by the public are presented as complex, interdependent, and reciprocal processes of translation. For the very first time, this book focuses on the artistic research involved in the company's international co-productions and features extensive empirical material in form of interviews with dancers, collaborators, and spectators, as well as ethnographic insights. This book introduces a praxeology of cultural and aesthetic translation as a viable key concept for research into dance and art